2013
DOI: 10.1017/jan.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding a commercial ammonia binding product De-Odorase™ on broiler chicken performance

Abstract: Ammonia production in commercial poultry sheds poses a problem for farmers as high levels can affect animal's respiratory health, resulting in hock and foot pad lesions and thereby affecting performance. A study was conducted to evaluate the suitability of whole, chopped and dried Yucca schidigera (De-Odorase™, Alltech Inc, USA) to reduce ammonia excretion from broilers and investigate the impact on broiler performance. Nine hundred and two, one-day-old Cobb broilers were randomly assigned to one of two diets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…Litter amendments are often used in poultry production to reduce litter pH to control ammonia and as an intervention method in houses with a recurring disease issue such as gangrenous dermatitis (Shepherd et al, 2010). Results of other authors showed that litter treatments with chemical or microbiological products have positive effects on litter condition by lowering pH value (Madrid et al, 2012), reducing ammonia emission (Kim & Patterson, 2003;Iwaczuk-Czernik et al, 2007;Li et al, 2008;Madrid et al, 2012), or litter moisture (Iwaczuk-Czernik et al, 2007;Lazarevic et al, 2014). Such litter treatments might have a positive (decreasing) effect on FPD occurrence (Purswell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Litter amendments are often used in poultry production to reduce litter pH to control ammonia and as an intervention method in houses with a recurring disease issue such as gangrenous dermatitis (Shepherd et al, 2010). Results of other authors showed that litter treatments with chemical or microbiological products have positive effects on litter condition by lowering pH value (Madrid et al, 2012), reducing ammonia emission (Kim & Patterson, 2003;Iwaczuk-Czernik et al, 2007;Li et al, 2008;Madrid et al, 2012), or litter moisture (Iwaczuk-Czernik et al, 2007;Lazarevic et al, 2014). Such litter treatments might have a positive (decreasing) effect on FPD occurrence (Purswell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Various litter amendments such as chemicals -aluminum sulfate (Madrid et al, 2012), sodium bisulfate (Nagaraj et al, 2007;Li et al, 2012), zeolite (Li etal., 2008), microbiological preparation (IwaczukCzernik et al, 2007), or a commercial ammonia binding agent (Lazarevic et al, 2014) are used to reduce litter moisture, pH and NH 3 emission in broiler houses. Some authors documented that such litter treatments might have positive effects on the occurrence of FPD (Nagaraj et al, 2007).…”
Section: Effect Of Litter On Development and Severity Of Footpad Dermmentioning
confidence: 99%
“…Emisi amonia adalah hasil dari proses fisik dan kimia yang kompleks, dengan tingkat emisi yang terkait dengan 4 faktor yaitu konsentrasi NH4 + , suhu internal, pH, dan efektivitas transportasi dari NH3 dari dalam metabolisme (Harper et al, 2010). Komplikasi dari paparan NH3 selama pemeliharaan unggas menyebabkan beberapa masalah antara penyakit pernapasan lainnya, kerusakan mata, lesi kaki, konversi pakan tidak efisien, penurunan Berat Badan, meningkatkan terjadinya penyakit Newcastle, keratoconjuctivitis, dan peningkatan jumlah Mycoplasma gallisepticum (Olanrewaju et al, 2008;Lazarevic et al, 2013).…”
Section: Gusma Gama Maradon Et Alunclassified
“…Various litter amendments, such as chemicals -aluminium sulfate (Zhang et al, 2011), sodium bisulfate (Nagaraj et al, 2007;Li et al, 2012) -dietary manipulations (Ferguson et al, 1998;Eichner et al, 2007), zeolite (Li et al, 2008), microbiological preparation (Iwańczuk-Czernik et al, 2007), and a commercial ammonia binding agent (Lazarevic et al, 2014), are used to reduce litter moisture, pH, and NH 3 emission in boiler houses. Litter treatments with chemical or microbiological products have positive effects on litter condition by lowering the pH (Zhang et al, 2011), and reducing ammonia emission (Iwańczuk-Czernik et al, 2007;Li et al, 2008;Zhang et al, 2011) or litter moisture (Iwańczuk-Czernik et al, 2007;Lazarevic et al, 2014).…”
mentioning
confidence: 99%
“…Litter treatments with chemical or microbiological products have positive effects on litter condition by lowering the pH (Zhang et al, 2011), and reducing ammonia emission (Iwańczuk-Czernik et al, 2007;Li et al, 2008;Zhang et al, 2011) or litter moisture (Iwańczuk-Czernik et al, 2007;Lazarevic et al, 2014).…”
mentioning
confidence: 99%